Metode uji sitotoksisitas biomaterial dengan bentuk scaffold padatan dan berpori spons - Octarina; Belatriks Kalangit, Ruth (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Three-dimensional scaffolds play a crucial role in supporting cell growth and tissue regeneration, especially in bone regenerative applications. Their utilization in dentistry demands effective cytotoxicity assessment, particularly for sponge-shaped scaffolds with a unique porous structure fostering a complex environment for cell growth. Therefore, the imperative lies in selecting cytotoxicity testing methods suitable for these characteristics. Relevant methods for such scaffolds include MTS, Alamar Blue, ATP, CCK-8, and MTT assays. MTS assay efficiently measures cell viability in a three-dimensional setting, while Alamar Blue and CCK-8 assays, with their water-soluble nature and high reproducibility, prove advantageous. ATP assay provides direct insights into cellular metabolic activity, and MTT assay assesses cell viability based on enzymatic capabilities. Due to their water-soluble characteristics, minimizing additional extraction steps, and ensuring high reproducibility, Alamar Blue and CCK-8 emerge as the most fitting options for cytotoxicity assessment in dentistry's sponge-shaped scaffolds.